PENGARUH POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN KARAKTER ANAK DALAM ERA DIGITAL - Isnaeni, Helmi Nur; Putri, Iraida; Anandasari, Novi (Jurnal Multidisipliner Bharasa, 2025)
The rapid development of digital technology has brought significant changesin various aspects of life, including the pattern of interaction between parents andchildren. This study aims to explore the influence of parental parenting on theformation of children's character in the midst of the dominance of the digital era. Themain focus of this research is to understand how moral values, empathy, andresponsibility are instilled by parents in the context of children's use of technology.The data was collected through in-depth interviews with 15 parents from varioussocio-economic backgrounds as well as observations on family dynamics in theirdaily lives. The results of the study show that authoritative parenting that combineswarmth and control tends to be more effective in forming positive characters inchildren compared to permissive or authoritarian parenting. Parents who are activelyinvolved in directing their children's use of technology, such as limiting screen timeand choosing educational content, have a greater impact on fostering attitudes ofdiscipline and responsibility. On the other hand, the lack of communication betweenparents and children regarding the use of digital media can lead to the emergence ofimpulsive behavior and a lack of empathy. These findings provide important insightsinto the urgency of adapting parenting styles that are in accordance with thechallenges of the times without abandoning fundamental values in charactereducation.